Effects of neurofeedback on major depressive disorder: a systematic review - Isabelly Cristine de Souza Dobbins; Murilo Bastos; Renan Cassiano Ratis; Weber Claúdio Francisco Nunes da Silva; Juliana Sartori Bonini (Einstein (São Paulo), 2023)
ABSTRACT Background Major depressive disorder is a difficult-to-treat psychological disorder. Approximately 30% of patients with major depressive disorder do not respond to conventional therapies; thus, the efficacy of alternative therapies for treating major depressive disorder, such as neurofeedback, a non-invasive neuromodulation method used in the treatment of psychiatric diseases, must be investigated. Objective We aimed to evaluate the efficacy of neurofeedback in minimizing and treating major depressive disorder and its application as a substitute to or an adjuvant with conventional therapies. Methods We searched for experimental studies published between 1962–2021 in Scopus, PubMed, Web of Science, and Embase databases and identified 1,487 studies, among which 13 met the inclusion exclusion criteria. Results We noted that not all patients responded to neurofeedback. Based on depression scales, major depressive disorder significantly improved in response to neurofeedback only in a few individuals. Additionally, the number of training sessions did not influence the results. Conclusion Neurofeedback can reduce depression symptoms in patients; however, not all patients respond to the treatment. Therefore, further studies must be conducted to validate the effectiveness of neurofeedback in treating major depressive disorder.